STUDI KORELASI PEMANFAATAN MEDIA SOSIAL DAN PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA PUTRI DI SMK AL ARIF GEMPOL - Umami, Siti Fithrotul (Rena Cipta Mandiri, 2025)
Knowledge about reproductive health among young women is still diverse and social media is a frequently accessed source of information. At SMK Al Arif, Gempol District, Pasuruan Regency, most teenagers actively use social media, but their level of knowledge about reproductive health is not optimal. This type of research is quantitative analytical with a cross-sectional approach involving 37 young women from grades X to XII. Purposive sampling technique was used for sample selection. The results of the research on the use of social media in the moderate category with less knowledge amounted to 9 respondents (24.3%) greater than those with sufficient and good knowledge levels, for the test results p value = 0.000 <0.05 has a meaning that there is a correlation between the use of social media and knowledge of reproductive health in young women with a Correlation Coefficient value = 0.710 indicating a strong correlation and a positive direction which means that the higher the use of social media, the better the knowledge of young women. Conclusion in this research is there is a positive correlation between the use of social media and knowledge of reproductive health.